(untitled) (Panauti Journal, 2025)
The penetration of capitalist and neoliberal economic policies has significantly transformed Nepal ‘s peasant economy, resulting in varied assessments of their socio-economic consequences. This study critically examines these transformations, with particular focus on changes in rural livelihoods, land tenure, and agricultural productivity over the period 1961–2023. To this end, a quantitative research design is employed, analyzing longitudinal secondary data from national and international agencies, including the Central Bureau of Statistics and World Bank Development Indicators, through time-series and pre-post comparative methods. Descriptive statistics are applied to clearly elucidate trends in landholding patterns, input usage, crop yields, household indebtedness, landlessness, income inequality, and agricultural employment. The findings reveal a marked decline in landholding size and the agricultural sector ‘s contribution to GDP, which occurs alongside increased rural vulnerability despite observable productivity gains. Furthermore, the growing reliance on remittances underscores a significant shift in livelihood strategies away from agriculture. Taken together, these structural changes underscore the persistence of dispossession and socio-economic disparities, which have been exacerbated by neoliberal reforms. Consequently, the study emphasizes the urgent need for agrarian reforms that prioritize equitable land distribution, improved rural credit access, and comprehensive social protection.